The fertility transition around the world - 1950-2005 - Holger Strulik; Sebastian Vollmer (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2010)
In this paper we analyze the distribution of fertility rates across the world using parametric mixture models. We demonstrate the existence of twin peaks and the division of the world's countries in two distinct components: a high-fertility regime and a low fertility regime. Whereas the significance of twin peaks vanishes over time, the two fertility regimes continue to exists over the whole observation period. In 1950 about two thirds of the world's countries belonged to the high-fertility regime and the rest constituted the low-fertility regime. By the year 2005 this picture has reversed. Within both the low- and the high-fertility regime the average fertility rate declined, with a larger absolute decline within the high-fertility regime. Visually, the two peaks moved closer together. For the low fertility-group we find both beta- and sigma- convergence but we cannot establish any convergence pattern for the high fertility regime. Overall our findings are difficult to reconcile with the standard view of a fertility trap but they support the 'differentiated take-off' view established in the Unified Growth literature.
Keywords: 330; Fertility; Convergence; Twin Peaks; Fertility Regimes; Unified Growth; Fruchtbarkeit; Demographischer Übergang; Entwicklungskonvergenz; Welt